Cutting performance and wear mechanism of honeycomb ceramic tools in interrupted cutting of nickel-based superalloys. Issue 13 (1st July 2021) - Yu, Weiwei; Ming, Weiwei; An, Qinglong; Chen, Ming
Abstract: Nickel-based superalloys are favored because of high fatigue strength, corrosion resistance and oxidation resistance. However, the characteristics of high hardness, poor heat dissipation and sticking make the machinability of nickel-based superalloys poor, which is more serious for interrupted processing. Therefore, honeycomb ceramic tools are utilized to turn GH4169. Cutting and impact force, wear patterns and mechanism of honeycomb ceramic tools are analyzed. The results demonstrate that the impact force is greater than the average cutting force. Fractures, chipping and adhesion are the main wear characteristics of honeycomb ceramic tools. Furthermore, adhesive, abrasive and diffusion wear are the main wear mechanisms.